Assessment of magnetic flux density properties of electromagnetic noninvasive phrenic nerve stimulations for environmental safety in an ICU environment - K. Friedrich Kuhn (Nature Portfolio, 2021)
Abstract Diaphragm weakness affects up to 60% of ventilated patients leading to muscle atrophy, reduction of muscle fiber force via muscle fiber injuries and prolonged weaning from mechanical ventilation. Electromagnetic stimulation of the phrenic nerve can induce contractions of the diaphragm and potentially prevent and treat loss of muscular function. Recommended safety distance of electromagnetic coils is 1 m. The aim of this study was to investigate the magnetic flux density in a typical intensive care unit (ICU) setting. Simulation of magnetic flux density generated by a butterfly coil was performed in a Berlin ICU training center with testing of potential disturbance and heating of medical equipment. Approximate safety distances to surrounding medical ICU equipment were additionally measured in an ICU training center in Bern. Magnetic flux density declined exponentially with advancing distance from the stimulation coil. Above a coil distance of 300 mm with stimulation of 100% power the signal could not be distinguished from the surrounding magnetic background noise. Electromagnetic stimulation of the phrenic nerve for diaphragm contraction in an intensive care unit setting seems to be safe and feasible from a technical point of view with a distance above 300 mm to ICU equipment from the stimulation coil.